2019
DOI: 10.1111/bph.14793
|View full text |Cite
|
Sign up to set email alerts
|

Ursolic acid promotes apoptosis and mediates transcriptional suppression of CT45A2 gene expression in non‐small‐cell lung carcinoma harbouring EGFR T790M mutations

Abstract: Background and Purpose In non‐small‐cell lung carcinoma (NSCLC) patients, the L858R/T790M mutation of the epithelial growth factor receptor (EGFR) is a major cause of acquired resistance to EGFR‐TKIs treatment that limits their therapeutic efficacy. Identification of drugs that can preferentially kill the NSCLC harbouring L858R/T790M mutation is therefore critical. Here, we have evaluated the effects of ursolic acid, an active component isolated from herbal sources, on erlotinib‐resistant H1975 cells that harb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 39 publications
(49 reference statements)
1
27
0
Order By: Relevance
“…UA is a natural pentacyclic triterpenoid that possesses anticancer activities against a variety of cancers in vitro and in vivo (17,18,22,24,26). For example, UA has been shown to significantly suppress xenograft tumor growth in a human lung cancer H1975 xenograft mouse model (24). UA exhibits a low toxicity in human normal lung epithelial BEAS-2B cells, and exerts minimal toxic effects on the kidney and liver tissues in mice (24).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…UA is a natural pentacyclic triterpenoid that possesses anticancer activities against a variety of cancers in vitro and in vivo (17,18,22,24,26). For example, UA has been shown to significantly suppress xenograft tumor growth in a human lung cancer H1975 xenograft mouse model (24). UA exhibits a low toxicity in human normal lung epithelial BEAS-2B cells, and exerts minimal toxic effects on the kidney and liver tissues in mice (24).…”
Section: Discussionmentioning
confidence: 99%
“…For example, UA has been shown to significantly suppress xenograft tumor growth in a human lung cancer H1975 xenograft mouse model (24). UA exhibits a low toxicity in human normal lung epithelial BEAS-2B cells, and exerts minimal toxic effects on the kidney and liver tissues in mice (24). Furthermore, UA has recently been promoted to enter clinical trials to investigate its effects on insulin sensitivity (phase II study) and muscle function in human sarcopenia (phase II and III studies) (52,53).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies further demonstrated that UA had more pharmacological effects, such as blocking the process of chronic disease (Yu et al 2017), radiosensitization (Yang et al 2015), neuroprotective (Habtemariam 2019), antidiabetic (Xu et al 2018), and antitumor (Zang et al 2014). Studies have confirmed that UA plays an antitumor role in a variety of tumours, including colorectal cancer (Kim et al 2018), breast cancer (Yin et al 2018), endometrial carcinoma (Achiwa et al 2013), and lung cancer (Yang et al 2019). UA plays an antitumor role in a variety of ways, including inhibition of proliferation, angiogenesis, invasion, metastasis, differentiation, and induction of tumour cell apoptosis (Zhang et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“… 2013 ), and lung cancer (Yang et al. 2019 ). UA plays an antitumor role in a variety of ways, including inhibition of proliferation, angiogenesis, invasion, metastasis, differentiation, and induction of tumour cell apoptosis (Zhang et al.…”
Section: Introductionmentioning
confidence: 99%